National, regional or industrial explanation for firms' deaths in the European Union since 2010 until 2014 - a shift-share application. (6th March 2019) - Shinkarenko, Kseniia; Nunes, Alcina; Khvatova, Tatiana
The concept of business closure is one of the most important in business demography. Traditionally, firms' closure has been associated with regional factors. Still, a region can have different from the nation aggregate rate of activity because it has a different mix of industries and/or because it enjoys comparatively more favourable local conditions. Thus, business closure may be driven by the business cycle, industrial composition as well as a regional advantage. So, the present work is dedicated to analyse the factors that may drive business closure in European Union countries between 2010 and 2014, and to find out which of them has/have been the most important one(s). For this purpose, a shift-share decomposition analysis of business closure will be applied. The results proved that regional component had the highest impact on firms' deaths during the investigated period of time for almost all countries included in the analysis.